Test method for evaluating performance of key material of electrochemical gas sensor
Patent Information
- Application Number
- CN202511998070.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-12-28
- Publication Date
- 2026-03-17
Smart Images

Figure CN121678804A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of gas sensor technology, and in particular to a testing method for evaluating the performance of key materials in electrochemical gas sensors. Background Technology
[0002] YSZ-based solid-state electrolyte gas sensors are an important type of electrochemical sensor, widely used in gas monitoring in high-temperature and high-vibration environments such as automotive exhaust gas monitoring, offering advantages such as high detection accuracy and good selectivity. However, because both the electrodes and electrolyte are solid-state, the applied operating voltage often experiences some losses during actual operation, leading to certain deviations in sensor performance.
[0003] In recent years, major research institutions have conducted studies on the impact of the working circuit resistance of solid electrolyte sensors. These studies mainly focus on the interface resistance between the electrode and the electrolyte. However, the working electrode itself also has a certain resistance due to the transport of protons and charges. When the sensor is working, the resistance and transport efficiency of the working electrode itself will lead to the loss of operating voltage, causing the sensor to deviate from its normal operating state and resulting in distorted detection results.
[0004] When the sensing electrode is in operation, there is a difference between its internal longitudinal and transverse resistance. The longitudinal resistance is directly related to the sensing signal and reflects the ion transport efficiency inside the electrode; while the transverse resistance indicates electrode wear and reflects electrode losses. To obtain a reliable electrochemical gas sensor, it is necessary to establish a performance evaluation method for key sensing materials to provide reliable support for sensor fabrication. Summary of the Invention
[0005] To address the shortcomings of existing technologies, this invention provides a testing method for evaluating the performance of key materials in electrochemical gas sensors. This method can accurately evaluate the resistance of the working electrode made from the sensor's functional materials, distinguish between the longitudinal and transverse resistance of the working electrode, determine the charge transport state of the electrode, and thus provide a reference for sensor fabrication.
[0006] The technical solution of this invention is as follows:
[0007] A testing method for evaluating the performance of key materials in electrochemical gas sensors includes the following steps:
[0008] (1) Preparation of the sensing sample: The key sensing material to be tested is printed on both sides of the solid electrolyte to form a four-electrode system sensing sample; the four-electrode system includes a working electrode, a counter electrode, an upper sensing electrode, a lower sensing electrode and a lead electrode; wherein, the working electrode is printed on one side of the solid electrolyte and the counter electrode is printed on the other side of the solid electrolyte; the upper sensing electrode and the lower sensing electrode are located on the upper and lower layers of the working electrode, respectively.
[0009] (2) Determine the working current density J0: Heat the sensing sample in an air atmosphere, apply different currents, and test the working potential V0, upper induced potential V1 and lower induced potential V2 respectively to form a VJ curve. Determine the working current density J0 based on the VJ curve.
[0010] (3) Measure and calculate the longitudinal and transverse resistances: Apply working current density J0 to the sensing sample, alternately introduce air and detection gas, and record the working potential V0 and induced potential V1 and V2 respectively; calculate the longitudinal resistance R1 = (V1-V2) / J0 of the working electrode; calculate the transverse resistance R2 = (V0-V1) / J0 of the working electrode.
[0011] (4) Material performance judgment: Calculate the ratio R1 / R2 of the longitudinal resistance to the transverse resistance of the working electrode in the air and the detection gas. When R1 / R2 is 1.1-10, the key sensing material is deemed qualified.
[0012] Furthermore, both the upper and lower sensing electrodes are annular and located outside the working electrode.
[0013] Furthermore, the working electrode is composed of Pt, Ni, Ti, or Cu, the counter electrode is composed of Pt, and the sensing electrode is composed of Au; the lead electrode is Pt or Au; and the solid electrolyte is yttrium-doped zirconium oxide.
[0014] Furthermore, in step (2), the sensing sample is placed in the air and heated to a temperature of 500-800℃.
[0015] Furthermore, in step (2), when performing the current density-potential test, the current value is 0-2A; in the formed VJ curve, the current density J is the ratio of the current to the working electrode area; in the VJ curve, the current density when the potential value difference is greater than 0.01V is determined as J0.
[0016] Furthermore, in step (3), the gas to be detected is nitrogen oxides, ethanol or hydrogen sulfide gas with a concentration of 50 ppm, and the remaining gas is nitrogen.
[0017] Furthermore, in step (1), the lead electrode is located at the center of the working electrode and the counter electrode, respectively.
[0018] The beneficial effects of this invention are as follows:
[0019] 1. The in-situ detection method for key materials of the electrochemical gas sensor of the present invention adopts a four-electrode system with two independent sensing electrodes located on the upper and lower layers of the working electrode, respectively. It can test the induced potential on the upper and lower surfaces of the working electrode separately, and has high detection accuracy.
[0020] 2. The sensing electrodes of the electrochemical gas sensor involved in the present invention are all annular and are respectively located on the outer sides of the upper and lower surfaces of the working electrode, which can increase the utilization rate of the working electrode.
[0021] 3. The lead electrode of the electrochemical gas sensor involved in the present invention is located at the center of the working electrode, the sensing electrode is annular and is located on the outer layer of the working electrode, and the transverse resistance of the working electrode can be determined by the working potential and the induced voltage on the upper surface.
[0022] 4. The in-situ detection process of the sensing sample formed by assembling the key sensing materials involved in the present invention includes the tests of the working potential and the induced potential of the working electrode. Among them, the ratio of the difference between the working potential and the induced potential on the upper surface to the current can calculate the transverse resistance of the working electrode, and the ratio of the difference between the induced potentials on the upper and lower surfaces to the current can calculate the longitudinal resistance of the working electrode. The detection method can distinguish the differences in the longitudinal and transverse resistances of the working electrode.
[0023] 5. The present invention involves the detection of sensing samples in air and detection gases, and provides evaluation indexes for the performance of key sensing materials. By limiting the ratio R1 / R2 of the longitudinal and transverse resistances of the working electrode, the detection performance of the working electrode can be optimized. When R1 / R2 is 1.1 - 10, the materials used in the sensor are qualified for detection. Description of the Drawings
[0024] Figure 1 It is a schematic diagram of the structure and detection of the sensing sample.
[0025] Figure 2 It is a top view of the working electrode of the sensing sample.
[0026] Figure 3 It is a schematic diagram of the sensing electrode of the sensing sample.
[0027] Figure 4 It is a top view of the counter electrode of the sensing sample.
[0028] Figure 5 It is a schematic flow diagram of the detection method of the present invention.
[0029] Figure 6 It is a V-J curve diagram of the sensing sample in Example 1.
[0030] In the figure, 1 - electrolyte layer, 21 - working electrode, 22 - lead electrode 1, 23 - upper sensing electrode, 24 - lower sensing electrode, 25 - counter electrode, 26 - lead electrode 2. Detailed Embodiments
[0031] Next, the present invention will be further described in combination with the drawings and specific embodiments.
[0032] The testing method for evaluating the performance of key materials in electrochemical gas sensors provided by this invention first requires printing the key sensing material to be tested onto both sides of a solid electrolyte to prepare a sensing sample forming a four-electrode system. For example... Figure 1 As shown, the sensing sample includes an electrolyte layer 1, a working electrode 21, an upper sensing electrode 23, a lower sensing electrode 24, a counter electrode 25, and lead electrodes 22 and 26. The working electrode 21 is printed on one side of the solid electrolyte 1, and the counter electrode 25 is printed on the other side of the solid electrolyte 1. The upper sensing electrode 23 is formed by printing on the upper surface of the working electrode 21, and the lower sensing electrode 24 is formed by printing between the lower surface of the working electrode 21 and the electrolyte layer 1. The working electrode 21 and the counter electrode 25 are led out through the lead electrodes 22 and 26, respectively, and connected to a current source. A top view of the working electrode 21 is shown below. Figure 2 As shown, schematic diagrams of sensing electrode 23 and sensing electrode 24 are as follows. Figure 3 As shown, the top view of electrode 25 is as follows Figure 4 As shown.
[0033] Both the upper sensing electrode 23 and the lower sensing electrode 24 are annular and located outside the working electrode 21. The lead electrode 22 is located at the center of the working electrode 21, and the lead electrode 26 is located at the center of the counter electrode 25. The working electrode 21 is composed of Pt, Ni, Ti, or Cu, the counter electrode 25 is composed of Pt, the sensing electrode is composed of Au, and the lead electrode is either Pt or Au. The solid electrolyte is yttrium-doped zirconium oxide (YSZ).
[0034] Main working principle:
[0035] During operation, the sensing sample is heated to 500-800℃; the sensing sample is placed in a detection gas environment, and a working current density J0 is applied to test the working potential V0, upper induced potential V1, and lower induced potential V2 of the circuit. Since the lead electrode 22 is located at the center of the working electrode 21, and the upper induced electrode 23 is annular and located on the outer upper surface of the working electrode 21, the difference between the working potential V0 and the upper induced potential V1 reflects the transverse voltage drop of the working electrode 21; since the lower induced electrode 24 is annular and located on the outer lower surface of the working electrode 21, the difference between the upper induced potential V1 and the lower induced potential V2 reflects the longitudinal voltage drop of the working electrode 21.
[0036] According to Ohm's law, the longitudinal resistance R1 = (V1 - V2) / J0, and the transverse resistance R2 = (V0 - V1) / J0. The longitudinal resistance R1 reflects the ion transport efficiency inside the working electrode and is directly related to the sensing signal; the transverse resistance R2 reflects the transverse loss of the working electrode. By comparing the longitudinal and transverse resistance ratios R1 / R2 in air and the detection gas environment, the characteristics of the key sensing materials can be determined. When R1 / R2 is between 1.1 and 10, it indicates that the working electrode has a suitable longitudinal and transverse resistance ratio, and the key sensing materials pass the test.
[0037] The detection method flow of the present invention is as follows: Figure 5 As shown, the specific steps include:
[0038] Example 1
[0039] A testing method for evaluating the performance of key materials in electrochemical gas sensors is as follows:
[0040] Step 1: Preparation of the sensor sample:
[0041] A lower sensing electrode 24 is formed by printing Au as the sensing electrode material on one side of a yttrium-doped zirconium oxide (YSZ) solid electrolyte, and a counter electrode 25 is formed by printing Pt as the counter electrode material on the other side of the solid electrolyte. The electrodes are then dried to form electrode sheet 1. A working electrode 21 is formed by printing Pt as the key sensing material to be measured on the upper surface of the lower sensing electrode 24 of electrode sheet 1, and the electrodes are then dried to form electrode sheet 2. An upper sensing electrode 23 is formed by printing Au as the sensing electrode material on the surface of the working electrode 21 of electrode sheet 2, and the electrodes are then dried to form electrode sheet 3. A lead electrode 22 and a lead electrode 26 are formed by printing at the center of the working electrode 21 and the counter electrode 25 of electrode sheet 3, forming a four-electrode sensing sample.
[0042] Step 2: Determine the operating current density J0:
[0043] (1) Connect the working electrode 21 and the counter electrode 25 of the above-mentioned sensing sample to a current source through lead electrodes 22 and 26, and connect the upper sensing electrode 23 and the lower sensing electrode 24 to a voltmeter.
[0044] (2) Air atmosphere, the gas content is 0; put the sensor sample to be tested into the detection chamber, introduce air atmosphere, and heat to 700℃ by heating device (such as heating table, tube furnace, muffle furnace, etc.).
[0045] (3) Apply a current of 0-2A to the four-electrode sensing sample using a current source, obtain the VI curve, and calculate the current density by the ratio of current to working electrode area to obtain the VJ curve (e.g., ...). Figure 6 (As shown). When the difference between V0 and V1, and between V1 and V2 is 0.01V, the corresponding current density J0 is 0.41mA·cm. -2 .
[0046] Step 3: Measure and calculate the longitudinal and transverse resistances:
[0047] The detection gas was nitrogen oxides at a concentration of 50 ppm, with the remaining gas being nitrogen. A current density J0 = 0.41 mA·cm² was applied to the sensing sample. -2Air and nitrogen oxide detection gas are alternately introduced, and the changes in working potential V0 and induced potentials V1 and V2 are recorded. The longitudinal resistance R1 of the working electrode is calculated according to the formula R1=(V1-V2) / J0, and the transverse resistance R2 of the working electrode is calculated according to the formula R2=(V0-V1) / J0.
[0048] Step 4: Material Performance Determination
[0049] The longitudinal and transverse resistivity ratio R1 / R2 in air is calculated to be 1.2, and in a nitrogen oxide atmosphere, R1 / R2 is 3.1. Since the R1 / R2 ratios in both air and nitrogen oxide atmospheres are within the range of 1.1-10, the test results for the key sensor material Pt are qualified.
[0050] Example 2
[0051] A testing method for evaluating the performance of key materials in electrochemical gas sensors is as follows:
[0052] Step 1: Preparation of the sensor sample:
[0053] A lower sensing electrode 24 is formed by printing Au as the sensing electrode material on one side of a yttrium-doped zirconium oxide (YSZ) solid electrolyte, and a counter electrode 25 is formed by printing Pt as the counter electrode material on the other side of the solid electrolyte. The electrodes are then dried to form electrode sheet 1. A working electrode 21 is formed by printing Cu as the key sensing material to be measured on the upper surface of the lower sensing electrode 24 of electrode sheet 1, and the electrodes are then dried to form electrode sheet 2. An upper sensing electrode 23 is formed by printing Au as the sensing electrode material on the surface of the working electrode 21 of electrode sheet 2, and the electrodes are then dried to form electrode sheet 3. A lead electrode 22 and a lead electrode 26 are formed by printing at the center of the working electrode 21 and the counter electrode 25 of electrode sheet 3, forming a four-electrode sensing sample.
[0054] Step 2: Determine the operating current density J0:
[0055] (1) Connect the working electrode 21 and the counter electrode 25 of the above-mentioned sensing sample to a current source through lead electrodes 22 and 26, and connect the upper sensing electrode 23 and the lower sensing electrode 24 to a voltmeter.
[0056] (2) Air atmosphere, the gas content is 0; put the sensor sample to be tested into the detection chamber, introduce air atmosphere, and heat to 500℃ by heating device (such as heating table, tube furnace, muffle furnace, etc.).
[0057] (3) A current of 0-2A was applied to the four-electrode sensing sample using a current source, and the VI curve was obtained. The current density was calculated by the ratio of the current to the working electrode area, and the VJ curve was obtained. When the difference between V0 and V1, and between V1 and V2 is 0.01V, the corresponding current density J0 is 0.2mA·cm. -2 .
[0058] Step 3: Measure and calculate the longitudinal and transverse resistances:
[0059] The detection gas was hydrogen sulfide at a concentration of 50 ppm, and the remaining gas was nitrogen. A current density J0 = 0.2 mA·cm² was applied to the sensing sample. -2 Alternately introduce air and hydrogen sulfide detection gas, and record the changes in working potential V0 and induced potentials V1 and V2. Calculate the longitudinal resistance R1 of the working electrode using the formula R1 = (V1 - V2) / J0, and calculate the transverse resistance R2 of the working electrode using the formula R2 = (V0 - V1) / J0.
[0060] Step 4: Material Performance Determination
[0061] The calculated longitudinal and transverse resistivity ratio R1 / R2 in air is 1.7, and in a hydrogen sulfide atmosphere, R1 / R2 is 2.3. Since the R1 / R2 ratios in both air and hydrogen sulfide atmospheres are within the range of 1.1-10, the test results for the key sensing material Cu are qualified.
[0062] As can be seen from Examples 1 and 2 above, the testing method provided by this invention is applicable to different working electrode materials (such as Pt, Cu, etc.) and different detection gases (such as nitrogen oxides, hydrogen sulfide, etc.), and can effectively evaluate the performance of key sensing materials at different operating temperatures (500-800℃). By calculating the longitudinal and transverse resistance ratio R1 / R2, the qualification of key sensing materials can be quantitatively determined, providing a reliable reference for the design and fabrication of electrochemical gas sensors.
[0063] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A test method for evaluating the performance of key materials for electrochemical gas sensors, characterized by, The method comprises the following steps: (1) Preparation of a sensing sample: A sensing key material to be tested is printed on both sides of a solid electrolyte to form a sensing sample of a four-electrode system; the four-electrode system comprises a working electrode, a counter electrode, an upper sensing electrode, a lower sensing electrode and a lead electrode; the working electrode is printed on one side of the solid electrolyte, and the counter electrode is printed on the other side of the solid electrolyte; the upper sensing electrode and the lower sensing electrode are located on the upper layer and the lower layer of the working electrode, respectively; (2) Determination of working current density J0: The sensing sample is heated in an air atmosphere, different currents are applied, the working potential V0, the upper sensing potential V1 and the lower sensing potential V2 are tested respectively, a V-J curve is formed, and the working current density J0 is determined according to the V-J curve; (3) Measurement and calculation of longitudinal and transverse resistances: The working current density J0 is applied to the sensing sample, and air and detection gas are alternately introduced, and the working potential V0 and the sensing potentials V1 and V2 are recorded respectively; The longitudinal resistance R1 of the working electrode is calculated as (V1-V2) / J0; The transverse resistance R2 of the working electrode is calculated as (V0-V1) / J0; (4) Material performance determination: The ratio R1 / R2 of the longitudinal resistance and the transverse resistance of the working electrode in air and in the detection gas is calculated, and when the R1 / R2 is 1.1-10, the sensing key material is determined to be qualified.
2. The test method of claim 1, wherein, In step (1), the upper sensing electrode and the lower sensing electrode are both ring-shaped and located outside the working electrode.
3. The test method of claim 1, wherein, In step (1), the working electrode is composed of Pt, Ni, Ti or Cu; the counter electrode is composed of Pt; the sensing electrode is composed of Au; and the lead electrode is Pt or Au.
4. The test method of claim 1, wherein, In step (1), the solid electrolyte is yttrium-doped zirconium oxide.
5. The test method of claim 1, wherein, In step (2), the heating temperature is 500-800℃.
6. The test method of claim 1, wherein, In step (2), the applied current value is 0-2A; in the V-J curve, the current density J is the ratio of the current to the working electrode area; in the V-J curve, the current density when the potential difference is greater than 0.01V is determined as J0.
7. The test method of claim 1, wherein, In step (3), the detection gas is nitrogen oxide, ethanol or hydrogen sulfide gas with a concentration of 50ppm, and the remaining gas is nitrogen.
8. The test method of claim 1, wherein, In step (1), the lead electrodes are respectively located at the centers of the working electrode and the counter electrode.